Knowledge of foot and mouth disease among dairy farmers in thrissur district and the constraints in adopting control measures. - Subin K Mohan (Department of Veterinary and Animal Husbandry Extension Education, College of Veterinary and Animal Sciences, 2009)
Dairy farmers generally had an ambivalent or neutral attitude towards FMD vaccination. Between FMD experienced and inexperienced there wasn’t a significant difference in the attitude. Attending seminars, group discussions and lecture classes on FMD was positively and significantly correlated with attitude. Awareness of symptoms and transmission, first aid and disease management and prevention and control measures were generally found to be either medium or low. However, FMD inexperienced had comparatively lower awareness. Media exposure, exposure to inter personal channels of communication, seminars and workshops attended were found significant in explaining variations in the general awareness of FMD. Regarding constraints faced by farmers in adopting control measures, the foremost one was farm families hiding or not reporting that their cattle was FMD affected. In the case of disease management, the foremost constraint reported was the much time consuming nursing process of affected animals. The most relevant constraints reported by the implementing officers of FMD vaccination programme were unwillingness of dairy farmers to vaccinate their animals due to reduction in milk yield, the laborious nature of door step vaccination and the possible chances of vaccination after effects like abscess formation, abortion and lameness.